Insight into 144 patients with ocular vascular events during VEGF antagonist injections - Shami M (Dove Medical Press, 2012)
Ahmad M Mansour1, Maha Shahin2, Peter K Kofoed3, Maurizio B Parodi4, Michel Shami5, Stephen G Schwartz6, Collaborative Anti-VEGF Ocular Vascular Complications GroupDepartment of Ophthalmology, 1American University of Beirut, Beirut, Lebanon, Rafic Hariri University Hospital, Beirut, Lebanon; 2Mansoura University, Mansoura City, Egypt; 3Glostrup Hospital, University of Copenhagen, Denmark, National Eye Clinic, Kennedy Center, Glostrup, Denmark; 4University Vita-Salute, Scientific Institute San Raffaele, Milan, Italy; 5Texas Tech University Health Sciences Center, Lubbock, TX, USA; 6Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Naples and Miami, FL, USAAim: To record ocular vascular events following injections of vascular endothelium growth factor (VEGF) antagonists.Methods: Collaborative multicenter case series (48 cases), literature reviews (32 cases), and reports to the FDA (64 cases) of patients that had vascular occlusions during anti-VEGF therapy were collected and analyzed.Results: A total of 144 cases of ocular vascular events were identified, with these diagnosed a median of 15 days after anti-VEGF injection. The majority of patients had pre-existing risk factors for cardiovascular events and nine patients had a prior history of glaucoma. Mean visual acuity dropped by 6.4 lines with severe visual loss after injection to NLP (five eyes), LP (six eyes), and HM (two eyes). The overall risk of ocular vascular events following a VEGF antagonist injection was 0.108% in the general population and 2.61% in the diabetic population. Mean retinal arterial constriction after intravitreal bevacizumab in 13 eyes was 21% (standard deviation = 27%), and mean retinal venous constriction was 8% (standard deviation = 30%).Conclusion: Ocular vascular events are rare during anti-VEGF therapy, but can lead to severe visual loss and may be caused by a number of factors including the vasoconstrictor effect of the drug, a post-injection rise of intraocular pressure, patient stress as a result of the procedure, and the patient's natural history of underlying ocular or systemic diseases. The diabetic population appears to have a tendency towards ocular vascular occlusions.Keywords: Bevacizumab, retinal artery occlusion, retinal vein occlusion, retinal capillary occlusion, ranibizumab